Four-step total synthesis of (+)-yaoshanenolides A and B - Thorat, Sagar S.; Palange, Megha N.; Kontham, Ravindar (ACS Omega, 2018)
A highly concise bioinspired four-step total synthesis of yaoshanenolides A and B possessing tricyclic spirolactone with an unusual 5'H-spiro-[bicyclo[2.2.2]-oct[2] ene-7,2'-furan]-5'-one scaffold is reported. This synthesis features high-yielding aldol-type addition of gamma-butyrolactone on to the aldehyde, exocyclic olefination of lactone derivative using Eschenmoser's salt, and highly facial-and endo-selective [4 + 2]-cycloaddition of fully functionalized 5-methylene-2(5H)-furanone with natural R-(-)-alpha-phellandrene. The approach allows access to yaoshanenolides A and B in four linear steps in 11 and 13% overall yield.